APLIKASI PELAWATAN JEMAAT DENGAN MENGGUNAKAN METODE HAVERSINE BERBASIS ANDROID - Abednego Rayhan Kusnadi; Florensa Rosani Br Purba (Servirisma, 2021)
To visit congregation which is carried out by several members of the congregation who are members of the visiting workgroup accompanied by a pastor from the church visited. This activity is a form of expression of love, concern, and sympathy for the people being cared for. And it is hoped that through this visit, the congregation who is being cared for will get strength, comfort, and help in facing the struggles they are facing. Along with the development of current technology which can help the wider community to find out a person's location through a given address. By using the haversine method, visitors can make visits to the church's residence with a fairly short time and distance because the haversine method has the advantage of being able to calculate the distance and time using two lines on the earth, namely longitude and latitude. The making of this application is to produce an Android-based mobile application using Google Map to get the location of the congregation's residence which will be carried out by the visit to the Terang Hidup GKI congregation, where the visit is one of the service programs of the Terang Hidup GKI church.